Theoretical identification of the superior anchoring effect and electrochemical performance of Ti2CS2 by single atom Zn doping for lithium–sulfur batteries - Wang, Mingyang; Mao, Jianjun; Pang, Yudong; Zhang, Xilin; Wang, Haiyan; Yang, Zongxian; Lu, Zhansheng; Yang, Shuting (Physical chemistry chemical physics : PCCP, 2023)
As one of the promising next-generation energy storage systems, lithium–sulfur (Li–S) batteries have been the subject of much recent attention. However, the polysulfide shuttle effect remains problematic owing to the dissolution of intermediate polysulfide species in the electrolyte and the sluggish reaction dynamics in Li–S batteries. To overcome these issues, this work reports an effective strategy for enhancing the electrochemical performance of Li–S batteries using single atom Zn doping on the S-terminated Ti2C MXenes (Ti2−xZnxCS2). Spin-polarized density functional theory (DFT) calculations were performed to elucidate the interactions of lithium polysulfides (LiPSs) and the Ti2−xZnxCS2 surface in terms of geometric and electronic properties, as well as the delithiation process of Li2S on the Ti2−xZnxCS2 surface. It is found that doping single atom Zn could induce a new Lewis acid-based sites, which could provide proper affinity toward LiPSs. Combined with the metallic character, a low Li diffusion barrier and high catalytic activity for the delithiation process of Li2S, makes Ti2−xZnxCS2 a promising cathode material for Li–S batteries. The results demonstrate the importance of surface chemistry and the electronic structure of MXenes in LiPSs’ adsorption and catalysis capability. We believe that our findings provide insights into the recent experimental results and guidance for the preparation and practical application of MXenes in Li–S batteries.